The urokinase plasminogen activator and its inhibitors PAI-1 nad PAI-2 in primary cutaneous melanoma - Markovič Božič, Jasmina (Radiology and oncology (Ljubljana), 2003)
Background. We investigated the differences in urokinase plasminogen activator(uPA) and its inhibitors type-1 and 2 (PAI-1/2) concentrations in clinically suspected nevi, primary cutaneous melanoma and normal skin and correlations with histopathological prognostic factors of primary melanoma. Patients and methods. Fifty-one patients were enrolled. The tissue concentrations of uPA, PAI 1 and PAI2 were quantified by enzyme-linked immunosorbent assay (ELISA). Results. Mean uPA and PAI-1 concentrations in melanomas were higher than in normal surrounding skin (uPA: 1.08; vs. 0.48 ng/mgp; PAI-1: 14.07 vs. 2.07 ng/mgp; p 0.05; PAI-1: p = 0.02). PAI-2 concentration was higher in normal surrounding skin than in nevi and melanomas(p > 0.05). Melanoma uPA, PAI-1 and PAI-2 concentrations correlated significantly with normal skin (r= 0.73, 0.54, 0.38 respectively). PAI 1 was significantly lower in melanomas of Breslow thickness 0.75 mm, Clark invasion > II,with ulceration and vascular invasion. Conclusions. Determination of uPA and PAI-1 can provide significant additional prognostic information for melanoma patients.
Keywords: Diagnosis; diagnostika; koža; Kožne novotvorbe; kožne spremembe; Melanom; Melanoma; Pathology; Plasminogen Activator Inhibitor 1; Plasminogen Activator Inhibitor 2; Plazminogen aktivator, inhibitor 1; Plazminogenski aktivator, inhibitor 2; Prognosis; Prognoza; Skin Neoplasms; Urokinase